Sanitary and Hygienic Status and Associated Factors Among Food and Drinking Establishments of Burayu Town, Oromia, Ethiopia - Alqeer Aliyo; Jonse Daba; Menelik Legese (SAGE Publishing, 2023)
Background Foodborne diseases (FBDs) are a major public health concern in both developed and developing countries, as they comprise a broad spectrum of diseases and account for a significant proportion of morbidities and mortalities worldwide. In Ethiopia, the food and drinking establishments contribute to the incidence of foodborne diseases often associated with outbreaks that end up threatening global public health security. Objective To assess sanitation and hygienic status and associated factors among food and drinking establishments in Burayu town, Oromia, Ethiopia, 2022 Methods An institution-based cross-sectional study design with a systematic sampling technique was used. Data were collected from 257 food and drinking establishments' managers/owners using questionnaires and observational checklists . Data were entered by Epi data version 3.1 and exported to BIM SPSS version 21 for data analyses. Both descriptive and analytic statistics were employed. Statistical significance was considered at a P value less than 0.05 at a 95% confidence interval. Results The study revealed that 47.9% of the food and drinking establishments were in poor sanitation and hygienic status. The study showed that male managers (AOR: 9.29, 95% CI: 2.97-21.14), managers less than 40 years old (AOR: 1.24, 95% CI: 1.03-4.36), more than five years services (AOR: 3.66, 95% CI: 1.66-8.07), lack of clean basin (AOR: 2.92, 95% CI: 0.10-11.47), absence of liquid waste drainage system installations (AOR: 3.26, 95% CI: 0.12-0.62) were significantly associated with poor sanitation and hygienic status of food and drinking establishments. Conclusion and Recommendation The findings indicated that high prevalence of poor sanitation and hygienic status of the food and drinking establishments. Therefore, the establishments should avail waste drainage system, clean basin, renew the establishment providing the service for many years and encourage female empowerment to fulfill and maintain sanitation and hygienic status of their establishments.